2021
DOI: 10.2174/0929867327666201109122025
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Targeted Cancer Chemoprevention by Flavonoids

Abstract: : Over the past several decades, plant-derived products (phytochemicals) have been suggested to possess immense therapeutic potential. Among these phytochemicals, different flavonoids have been reported for their potent anticancer activity. To exhibit their anticancer potential, these flavonoids modulate different signaling pathways. Among these pathways, the mammalian target of rapamycin (mTOR) and associated phosphatidyl-inositiol 3-kinase (PI3K)/protein kinase B (Akt) signaling cascade has been suggested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Natural compounds obtained from plant sources have recently garnered interest due to their easy availability, non-toxic/low adverse effects, cost-effectiveness, and ability to modulate multiple pathways [8]. Among the natural compounds, flavonoids have gained attention as anticancer agents, and are documented as being effective against various types of cancer [9,10]. Flavonoids are of low-molecular-weight, comprising polyphenolic compounds, classified into six groups-isoflavonoids, flavanones, flavanols, flavonols, flavones, and anthocyanidins [11].…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds obtained from plant sources have recently garnered interest due to their easy availability, non-toxic/low adverse effects, cost-effectiveness, and ability to modulate multiple pathways [8]. Among the natural compounds, flavonoids have gained attention as anticancer agents, and are documented as being effective against various types of cancer [9,10]. Flavonoids are of low-molecular-weight, comprising polyphenolic compounds, classified into six groups-isoflavonoids, flavanones, flavanols, flavonols, flavones, and anthocyanidins [11].…”
Section: Introductionmentioning
confidence: 99%
“…Daidzein is a 7-hydroxy-3-(4-hydroxyphenyl) chromen-4-one, ubiquitously found in fruits, nuts, soybeans, and related products (Das et al, 2020;Islam et al, 2020). The daidzein leads to slight augmentation in micronucleus development at 75 μM concentration in V79 cells (Di Virgilio, Iwami, Wätjen, Kahl, & Degen, 2004).…”
Section: Daidzeinmentioning
confidence: 99%
“…Epigallocatechin-3-gallate is the core catechin present in green tea (Suhail, Parveen, Husain, & Rehan, 2019;Tabrez et al, 2020). Various studies reported different bio-physiological properties of EGCG ranging from antioxidative (Lambert & Elias, 2010;Nikoo, Regenstein, & Gavlighi, 2018), cytoprotective (Islam et al, 2020;Moravcova, Cervinkova, Kucera, Mezera, & Lotkova, 2014), antiinflammatory (Byun et al, 2014;Tabrez et al, 2013), and anti-fibrotic (Tsai et al, 2019;Yumei, Zhou, Zheng, & Chen, 2006). Kucera et al (2015) reported concentration-dependent toxicity of EGCG from 10 μM, whereas 5 μM concentration was suggested as a safer dose for cultured liver cells.…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
See 2 more Smart Citations